A Novel Assay to Identify the Trafficking Proteins that Bind to Specific Vesicle Populations. Issue 1 (1st December 2015) - Bentley, Marvin; Banker, Gary
Abstract: Here we describe a method capable of identifying interactions between candidate trafficking proteins and a defined vesicle population in intact cells. The assay involves the expression of an FKBP12‐rapamycin binding domain (FRB)–tagged candidate vesicle‐binding protein that can be inducibly linked to an FKBP‐tagged molecular motor. If the FRB‐tagged candidate protein binds the labeled vesicles, then linking the FRB and FKBP domains recruits motors to the vesicles and causes a predictable, highly distinctive change in vesicle trafficking. We describe two versions of the assay: a general protocol for use in cells with a typical microtubule‐organizing center and a specialized protocol designed to detect protein‐vesicle interactions in cultured neurons. We have successfully used this assay to identify kinesins and Rabs that bind to a variety of different vesicle populations. In principle, this assay could be used to investigate interactions between any category of vesicle trafficking proteins and any vesicle population that can be specifically labeled. © 2015 by John Wiley & Sons, Inc.